Organizational Culture in the Source-Based Waste Management Education and Vocational Program at Petitenget Temple (International Journal of Social Studies, 2026)
Waste management problems in tourism areas and sacred religious spaces require management approaches that are not merely technical in nature, but also address cultural and communication dimensions. This study aims to analyze cultural, structural, and organizational communication barriers in the implementation of the source-based waste management education and vocational program at Petitenget Temple, as well as to formulate strategies for strengthening organizational culture to enhance the program’s sustainability. This research employs a descriptive qualitative method with a phenomenological approach. Data were collected through in-depth interviews with 10 informants consisting of 5 main informants and 5 supporting informants, field observations, and a literature review. The data were analyzed thematically through systematic stages of data reduction, data display, and conclusion drawing. The results indicate that the main obstacles in the implementation of the program include the low internalization of waste segregation culture in religious practices, limited facilities and managerial resources, and the suboptimal pattern of persuasive communication directed at worshippers and visitors. Nevertheless, the education and vocational program has generated cognitive effects in the form of increased knowledge, affective effects in the form of growing environmental awareness, and behavioral effects in the form of the initial practice of waste segregation, although these changes have not yet occurred evenly. Effective strategies for strengthening organizational culture are realized through associative techniques linked to the values of Tri Hita Karana, message structuring techniques, and integrative techniques through collaboration among traditional institutions and government actors. This study concludes that the success of source-based waste management in traditional institutions is strongly determined by the capacity for organizational culture transformation and the effectiveness of persuasive communication based on local values. Theoretically, this study expands the scope of organizational communication and environmental communication within the context of traditional–religious institutions. Practically, the findings of this study may serve as a basis for formulating more contextual and sustainable culture-based waste management policies, particularly in religious tourism areas.